2021
DOI: 10.1142/s021759592140025x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rescheduling Algorithm for the Airline Recovery with Flight Priorities and Airport Capacity Constraints

Abstract: Many flights experience delays at the airport due to bad weather, temporary closures of airports, unscheduled maintenance, etc., which emphasizes the urgent need for disruption management. It is widely accepted for Chinese airline companies to determine the flight timetable according to the lexicographic preference of flight priorities. Flight schedulers usually deal with the preceding flights as important as the latter flight of a higher priority. In this paper, we propose a build-in flight feasibility verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Tian et al ( 31 ) suggested an enhanced column generation method to optimize the scheduling of disrupted flights, reducing the airline’s economic loss while boosting operational efficiency and providing a foundation for decision making. Ji et al ( 32 ) introduced a built-in flight feasibility verification technique to calculate the flight timetable in disruption management based on the lexicographic preference of flight priority.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tian et al ( 31 ) suggested an enhanced column generation method to optimize the scheduling of disrupted flights, reducing the airline’s economic loss while boosting operational efficiency and providing a foundation for decision making. Ji et al ( 32 ) introduced a built-in flight feasibility verification technique to calculate the flight timetable in disruption management based on the lexicographic preference of flight priority.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liang considered the aircraft recovery problem with airport capacity constraints and maintenance flexibility, and proposed a column generation heuristic method to solve it [15][16][17][18][19]. Ji considered the flight priority and airport capacity constraints and proposed a built-in flight feasibility verification algorithm to improve the rescheduling algorithm [20].…”
Section: Introductionmentioning
confidence: 99%
“…Aircraft pose estimation is a fundamental and challenging vision task that is crucial for many downstream tasks, such as intelligent airport security monitoring [ 1 ], decreasing aircraft crashes with airport surfaces [ 2 , 3 , 4 ], assisting subsequent airport control decisions [ 5 , 6 ], and establishing digital twin airports [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%